GAMBARAN PERILAKU MEROKOK PADA USIA REMAJA AWAL (10-14) DENGAN TINGKAT MOTIVASI BERPRESTASI SISWA - Handayani, Sri Eka; Prasetia, Muhammad Eka (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
This research is a qualitative descriptive study which aims to describe the smoking behavior of early adolescents (10-14) with the level of achievement motivation of Students SMPN XX in Banjarmasin. The research subjects were Guidance and Counseling Teachers at SMPN XX in Banjarmasin, The students of SMPN XX in Banjarmasin and Home room teacher of SMPN XX in Banjarmasin. Data was collected using interview, observation and documentation methods after the data was obtained and then analyzed descriptively qualitatively and also matched the answers of each informant from the results of interviews with informants then the data was validated using triangulation techniques. The target of this study is expected to be able to do community service, especially early adolescents (10-14) so that they understand that smoking not only affects physical health but also affects brain performance, which can cause decreased thinking power so that motivation for achievement also decreases.